Agility speed concentration effects on student ball dribbling skills in physical education context: a literature review - Zulpanero Zulpanero; Alnedral Alnedral (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to analyze the roles of agility, speed, and concentration in football and futsal dribbling skills through an integrated perspective. A narrative literature review was conducted on 15 national and international studies published between 2018 and 2025, including correlational, experimental, and pre–post intervention designs, with thematic synthesis applied to identify patterns in the interaction between physical and cognitive factors. Findings indicate that agility, particularly change-of-direction ability and balance, is the primary determinant of dribbling performance, while speed enhances execution efficiency and concentration supports perceptual–cognitive control. Integrated training combining agility drills, acceleration exercises, and cognitive tasks in small-sided or game-like settings effectively improves dribbling ability. The study concludes that dribbling is a multidimensional skill emerging from the interaction of physical and cognitive components, and training programs should reflect this integration, while further longitudinal and well-controlled intervention studies are needed to examine the transfer of these improvements to competitive performance.